Host Cell Signalling and Leishmania Mechanisms of Evasion - Marina Tiemi Shio; Kasra Hassani; Amandine Isnard; Benjamin Ralph; Irazu Contreras; Maria Adelaida Gomez; Issa Abu-Dayyeh; Martin Olivier (Journal of Tropical Medicine)
Leishmania parasites are able to secure their survival and propagation within their host by altering signalling pathways involved in the ability of macrophages to kill pathogens or to engage adaptive immune system. An important step in this immune evasion process is the activation of host protein tyrosine phosphatase SHP-1 by Leishmania. SHP-1 has been shown to directly inactivate JAK2 and Erk1/2 and to play a role in the negative regulation of several transcription factors involved in macrophage activation. These signalling alterations contribute to the inactivation of critical macrophage functions (e.g., Nitric oxide, IL-12, and TNF-α). Additionally, to interfere with IFN-γ receptor signalling, Leishmania also alters several LPS-mediated responses. Recent findings from our laboratory revealed a pivotal role for SHP-1 in the inhibition of TLR-induced macrophage activation through binding to and inactivating IL-1-receptor-associated kinase 1 (IRAK-1). Furthermore, we identified the binding site as an evolutionarily conserved ITIM-like motif, which we named kinase tyrosine-based inhibitory motif (KTIM). Collectively, a better understanding of the evasion mechanisms utilized by Leishmania parasite could help to develop more efficient antileishmanial therapies in the near future.